Analisis Akuntansi Zakat Dalam Meningkatkan Akuntabilitas Pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Deli Serdang - Andani, Nova; Syafina, Laylan (Balance : Jurnal Akuntansi dan Manajemen, 2022)
The accountability of an institution affects the level of trust of muzakki in paying zakat. Accountability can be realized by compiling financial reports in accordance with zakat accounting standards, namely PSAK 109. The purpose of the research conducted by the author is to find out how zakat accounting increases the accountability of the National Amil Zakat Agency (BAZNAS) Deli Serdang district. The method used in this study is qualitative and the source of data comes from interviews with staff and financial reports in the form of reports on the receipt and distribution of the National Amil Zakat Agency (BAZNAS) Deli Serdang district. In preparing financial reports, BAZNAS Deli Serdang Regency has not fully complied with PSAK 109, this has an impact on accountability which causes zakat receipts to be not optimal. To achieve this, it is necessary to conduct training for the Human Resources of BAZNAS Deli Serdang Regency so that they can provide an understanding of how to prepare financial reports in accordance with PSAK 109